An Analysis of the Impact of State Income Tax Rates and Bases on Foreign Investment. - Moore, Michael L.; Steece, Bert M.; Swenson, Charles W. (The Accounting Review, 1987)
Abstract ABSTRACT: This study investigates the influence of both the state corporate income tax rate and the form of the income tax base structure on foreign investment in manufacturing assets. An econometric model of foreign investment is derived from a supply-oriented theory of regional investment, That is, the decision to develop productive capacity in one region as opposed to another is due to regional advantages. Empirical results suggest that tax structures that use the unitary method of accounting have a substantial impact on the amounts of foreign investment. On the other hand, business income tax rates appear to have little impact.